The hypervariable region 4 (HV4) and position 93 of the α chain modulate CD1d‐glycolipid binding of iNKT TCRs. Issue 7 (12th May 2015) - Paletta, Daniel; Fichtner, Alina Suzann; Hahn, Anne Maria; Starick, Lisa; Beyersdorf, Niklas; Monzon‐Casanova, Elisa; Mueller, Thomas D; Herrmann, Thomas
<x xml:space="preserve">Abstract</x> TCRs of invariant NKT (iNKT) cells bind α‐galactosylceramide (αGC) loaded CD1d in a highly conserved fashion and show a characteristic TCR gene usage: An "invariant" α chain with a canonical AV14/AJ18 rearrangement in mice (AV24/AJ18 in humans) is paired with β chains containing characteristic Vβ segments. In the rat, a multimember AV14 gene family increases the variability within this system. This study characterizes CD1d binding of rat AV14 gene segments in TCR transductants as well as CD1d binding and iNKT TCR expression of expanded polyclonal F344 rat iNKT populations. It defines an important role of position 93 at the V‐J transition for TCR avidity and species cross‐reactivity of the rat iNKT TCR. Furthermore, for the first time we identified variability within the fourth hypervariable loop (HV4) of the α chain as a modulator of CD1d:αGC binding in rat and mouse. Additionally, we confirmed the importance of the CDR2β for CD1d:αGC binding, but also show that the CDR3β may even have opposite effects on binding depending on the pairing α chain. Altogether, we characterized naturally occurring sources of variability for the iNKT TCR and speculate that they rather level than increase the largely germline encoded differences of iNKT TCR ligand avidity.